Wound-healing potential of the fruit extract of Phaleria macrocarpa - Abood, W.N.; Al-Henhena, N.A.; Abood, A.N.; Al-Obaidi, M.M.J.; Ismail, S.; Abdulla, M.; Al Bartan, R. (Association of Basic Medical Sciences of Federation of Bosnia and Herzegovina, 2015)
The wound-healing potential of Phaleria macrocarpa was evaluated by monitoring the levels of inflammatory mediators, collagen, and antioxidant enzymes. Experimentally, two-centimeter-wide full-thickness-deep skin excision wounds were created on the posterior neck area of the rats. The wounds were topically treated with gum acacia as a vehicle in the control group, intrasite gel in the reference group, and 100 and 200 mg/mL P. macrocarpa ‎fruit extract in the treatment group. Granulation tissues were excised on the 15th day and were further processed for histological and biochemical analyzes. Wound healing was evaluated by measuring the contractions and protein contents of the wounds. Cellular redistribution and collagen deposition were assessed morphologically using Masson’s trichrome stain. Superoxide dismutase (SOD) and catalase (CAT) activities, along with malondialdehyde (MDA) level were determined in skin tissue homogenates of the dermal wounds. Serum levels of transforming growth factor beta 1 (TGF-β1) and tumor necrosis factor alpha (TNF-α) were evaluated in all the animals. A significant decrease in wound area was caused by a significant increase in TGF-β1 level in the treated groups. Decrease in TNF-α level and increase in the collagen formation were also observed in the treated groups. Topical treatment with P. macrocarpa fruit extract increased the SOD and CAT activities in the healing wounds, thereby significantly increasing MDA level. The topical treatment with P. macrocarpa fruit extract showed significant healing effect on excision wounds and demonstrated an important role in the inflammation process by increasing antioxidant enzyme activities, thereby accelerating the wound healing process and reducing tissue injury.